PERANCANGAN VIRTUAL PRIVATE NETWORK DENGAN PROTOKOL PPTP MENGGUNAKAN MIKROTIK UNTUK KEBUTUHAN REMOTE ACCESS - Vicky Phang; Endah Setyaningsih (Power Elektronik : Jurnal Orang Elektro, 2021)
Abstract  Internet has become an essential requirement for communication. By using the internet, it is possible for someone to get information anytime and anywhere. The internet is also used in local networks. The local network connects personal devices and workstations in an organization for the use of shared resources. The local network cannot be accessed from outside carelessly. A Virtual Private Network (VPN) allows devices outside the local network to connect using a public network anywhere on the condition that the device is connected to the internet. Therefore, in this journal a VPN network with a Point-to-Point Tunneling Protocol (PPTP) is designed using a MikroTik router. The PPTP protocol adds data security in these networks. A VPN network is designed to connect a total of two computers, one in the local network and one outside the local network. The VPN account that is created is for one device only. Computers on the local network use the Windows 10 operating system while computers outside the network use the Windows 7 operating system. Devices on the local network are connected using a straight type UTP cable with an RJ45 connector. The router used is the MikroTik hAP lite RB941-2nd router. The router is connected to a public network with an IP address of 103.83.174.25. The media used to configure the MikroTik router is WinBox version 3.27 (64-bit).